MoS2 reinforced PEEK composite for improved aqueous boundary lubrication - Xin Hou; Pengpeng Bai; Jingyang Li; Yuanzhe Li; Hui Cao; Xiangli Wen; Yonggang Meng; Liran Ma; Yu Tian (Friction, 2023)
Abstract Polyether-etherketone (PEEK) is a corrosion-resistant material that has been widely used in aqueous lubrication. However, its anti-wear performance must be improved for its application in the industry. In this study, to improve the anti-wear performance of PEEK for aqueous boundary lubrication, PEEK/MoS2 composites were prepared by ball-milling and spark plasma sintering processes. A competitive MoS2 mechanism between the low shear strength property and the role of promoting wear debris generation influences the anti-wear performance of PEEK/MoS2 composites. Experiments demonstrated that the coefficients of friction (COF) and wear rate of PEEK composite with 0.25 wt% MoS2 were significantly reduced 68% and 94%, respectively. Furthermore, this was the first time that a PEEK composite could achieve a COF of less than 0.05 in aqueous boundary lubrication. Its anti-wear performance was verified to be better than that of PEEK/carbon fiber (CF) and Thordon composites. The PEEK/MoS2 composite may be a potential material for underwater equipment because of its outstanding anti-wear performance in aqueous boundary lubrication.